A case report of atypical sleep in an ischemic stroke patient with psychiatric symptoms caused by olanzapine - Zhao, Huixin; Li, Shuang; Wang, Yanmei (Frontiers in Neurology, 2023)
Antipsychotics, tricyclic and 5-hydroxytryptamine reuptake inhibitors (SSRI) and 5-hydroxytryptamine and norepinephrine reuptake inhibitor (SNRI) antidepressants, and monoamine oxidase inhibitors can produce dream-rendering behaviors and/or dystonic deregulation during REM sleep. Acute episodes are also seen with withdrawal from alcohol or sedative-hypnotics, and the use of tricyclic and SSRI antidepressants. In this article, we present a case of olanzapine treatment of a patient with cerebrovascular disease with psychobehavioural symptoms. The patient was an elderly patient who developed psychobehavioural symptoms after a sudden cerebral infarction. Initially, his symptoms improved when he took olanzapine (5 mg orally once/night). However, the patient subsequently developed symptoms of hypersomnia when he continued to take olanzapine, and the symptoms of hypersomnia gradually worsened as the dose of olanzapine was gradually increased. Benzodiazepines are often used to treat anomalous sleep, and clonazepam is one of the commonly prescribed drugs. In this case, the patient’s abnormal sleep behavior was alleviated after treatment with clonazepam. As an atypical antipsychotic drug, olanzapine has been reported to cause abnormal sleep behavior during clinical use, and only one case has been reported in China. Clinicians should be aware that heteromorphic sleep can occur in patients treated with olanzapine.